Жанрова специфіка віршованого листа - Назарець, Віталій Миколайович (Східноєвропейський національний університет імені Лесі Українки, 2013)
Статтю присвячено дослідженню одного із жанрово-тематичних різновидів адресованої лірики – віршо-ваного листа. На матеріалі поетичних текстів української адресованої лірики ХІХ–ХХ ст. досліджується жанрова специфіка віршованого листа, виокремлюються його генологічні художні модифікації.This article deals with research of one of the genre-thematic variety of addressed lyrics – poetic letter. Addressed lyrics is considered as supergenre formation which includes lyric works with accented dialogic aim oriented on communication with intratextual addressee (poetic letter, poetic epistle, dedication). The genre specifics of the poetic letter is investigated and its two genological artistic modifications are defined on the material of poetic texts of Ukrainian addressed lyrics of XIX – ХХ centuries: letter of informative type and letter of reflective type. Informative-communicative structure, genre reflections including lyric title, composition and thematic peculiarities of the certain artistic modifications of a poetic letter, their sender and addressee are characterized.
Keywords: адресована лірика; жанрова специфіка; віршований лист; лист інформативного типу; лист рефлективного типу; автор; адресат